"Estrés laboral y calidad del cuidado enfermero al prematuro. Chiclayo" - Vera Mechán, Angélica Brigida (2016)
This quantitative research descriptive correlational, cross-sectional, applied in intensive and intermediate care neonatology Lambayeque Regional Hospital, during the months of May to August 2015; in order to determine the relationship between the level of job stress and quality of nursing care to premature. The sample population consisted of 30 nurses who met the inclusion criteria. Questionnaire was used to determine the level of job stress and Caruana Reig nurse and Observation Guide to determine the quality of nursing care to premature for data collection. The obtained information is presented in simple tables and double entry. For statistical analysis the chi-square statistical test (x2) was used. The conclusions were: 58.1 percent of nurses had moderate stress, high stress 38.7 percent and 3.2 percent mild stress. The quality of care to premature is regular in 48.4 percent of nurses and 51.6 percent good. The stress level of professional nursing is not significantly related to quality of care provided to premature.